MATERIAL SELECTION ANALYSIS AND MAGNET SKEWING TO REDUCE COGGING TORQUE IN PERMANENT MAGNET GENERATOR - Sepannur Bandri, M. Aldi Tio (Menara Ilmu, 2018)
Cogging Torque is a pounding (torque opposite the direction of rotator generator)when rotating the rotor that causes the rotor is difficult to rotate by hand and can interferewith the rotation of the generator at the start, causing vibrations and disturbing sounds.Cogging is a characteristic attached to a permanent magnet generator (GMP) caused bythe geometry of the generator. Cogging torque may affect start ability, generate noise andmechanical vibrations when GMP is installed in wind turbines. Therefore cogging GMPshould be made as small as possible (coggingless), one way is to tilt (Skewing) permanentmagnet. Simulation using magnet software to know the magnitude of the cogging torquecaused by the rotation of the rotor on the generator. The cogging torque simulation resultsare further validated by the starting torque on the GMP testing method using materialchanges and magnetic skewing. The best magnetic slope is achieved when the magneticslope is 7.5 °, because in this position also the highest cogging torque (9.951905191 xNm) is found in model 3 material A skewing magnet (7.5º) with Cr-10 core materialand NdFeb magnetic magnet, while the lowest cogging value (1.17512009 x Nm) isfound in model 3 material A magnetic skewing (7.5º) with core material M250-35A andpermanent magnet NdFeb.Keywords: Generator, Cogging, Skewing, Torque